Care in patients with epidermal necrolysis in burn units. A nursing perspective. Issue 8 (December 2018) - Lerma, V.; Macías, M.; Toro, R.; Moscoso, A.; Alonso, Y.; Hernández, O.; de Abajo, F.J.
Highlights: Epidermal necrolysis care varies in burn units. Few burn units in Spain have nursing care protocols on epidermal necrolysis. Some interventions are outdated and subject to improvement. Recording of pain assessment in sedated patients is poor in most burn units. There is a general need for standardized nursing care guidelines on the disease. Abstract: Objective: To describe how nursing care is delivered to patients with epidermal necrolysis in burn units/specialized units in Spain and a selection of countries. Method: Descriptive cross-sectional study. Data were collected through a structured questionnaire which was sent to nurse managers in all burn units in Spain and a selection of countries. Descriptive statistics was used to summarize the results. Results: All BU/SUs in Spain (n = 12) and seven BU/SUs from a selection of countries completed the questionnaire. A lack of specific nursing protocols on Epidermal Necrolysis was observed in most burn units in Spain. Skin cleansing techniques such as showering were only reported by participants from Spain. Use of antiseptics was less frequent in other countries. Conservative skin management was the most extended practice reported by all participants. The use of vaginal molds to prevent synechiae and coverage of the ocular surface with amniotic membrane to minimize sequelae were rarely reported. Pain assessment was not always documented in sedated patients and few participants reported the use of specific scales for this purpose. All nurses agreed in the need for consensus nursing care guidelines on the disease. Conclusions: Nursing care in patients with epidermal necrolysis varied between burn units in Spain. Differences and similarities were observed when compared with burn units in other countries. Genital and ocular care were outdated in all BU/SUs. Pain assessment documentation was suboptimal. Evidence-based nursing care guidelines were generally demanded by all participants to help reduce mortality and morbidity of this rare and often devastating disease.